2017
DOI: 10.1016/j.euf.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Shape and Architecture in Benign Fields Predict Biochemical Recurrence in Prostate Cancer Patients Following Radical Prostatectomy: Preliminary Findings

Abstract: Background Gleason scoring represents the standard for diagnosis of prostate cancer (PCa) and assessment of prognosis following radical prostatectomy (RP), but it does not account for patterns in neighboring normal-appearing benign fields that may be predictive of disease recurrence. Objective To investigate (1) whether computer-extracted image features within tumor-adjacent benign regions on digital pathology images could predict recurrence in PCa patients after surgery and (2) whether a tumor plus adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 25 publications
4
51
0
Order By: Relevance
“…These nuclear shape/texture features are intended to capture the disorder of nuclear shape and texture, attributes that have been previously shown to be implicated in tumor aggressiveness [25]. …”
Section: Methodsmentioning
confidence: 99%
“…These nuclear shape/texture features are intended to capture the disorder of nuclear shape and texture, attributes that have been previously shown to be implicated in tumor aggressiveness [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Beck et al 88 looked at cells in the context of their spatial locations within the surrounding tumour stroma and showed associations between stromal features and survival in breast cancer. Lee et al 89 have also demonstrated that computational analysis of tumour-adjacent benign tissue in prostate cancer can reveal information that is typically ignored by pathologists but is associated with progression-free survival. More recently, Lu et al showed that features that describe nuclear shape and nuclear orientation were strongly associated with survival in both oral cancers 90 and early-stage oestrogen receptor-positive breast cancers 91 .…”
Section: Applications In Drug Discoverymentioning
confidence: 99%
“…51 Interestingly, pathologists do not currently spend a great deal of time interrogating stromal architecture, but recent results suggest that tumors adjacent normal appearing regions might contain substantial prognostic information. 52 Future work will include validation of our approach on a larger independent test set, evaluation of our approach on other use cases apart from BCC, as well as the consideration of new visual and architectural nuclear features.…”
Section: Discussionmentioning
confidence: 99%